Life quality in Russia: a brief overview - D. A. Ermilina (Вестник университета, 2022)
The life quality is a fundamental characteristic by which it is possible to assess the level of socio-economic development of the territory for which it is assessed. The main purpose of the study is to assess the key socio-economic parameters that affect the life quality in Russia. Methods of system analysis, classification and generalization were used in the study. The analysis of the main macroeconomic indicators affecting the quality of life in our country, such as gross domestic product, inflation rate, unemployment rate, the volume of credit resources issued, household consumption expenditures, is carried out. The main trends of their changes are revealed. The article convincingly shows that the life quality is formed under the influence of external and internal factors, which together reflect the living standard state of the population (material well-being, consumption of goods). The values of the vast majority of key factors affecting the life quality of Russian population have negative dynamics. To change the situation, it is necessary to develop a comprehensive system of measures, where the key role is assigned to state regulation, which actively responds to the transformations taking place in the socio-economic environment.